Bank mergers, competition and liquidity - Elena Carletti; Philipp Hartmann; Giancarlo Spagnolo (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
We model the impact of bank mergers on loan competition, reserve holdings and aggregate liquidity. A merger changes the distribution of liquidity shocks and creates an internal money market, leading to financial cost efficiencies and more precise estimates of liquidity needs. The merged banks may increase their reserve holdings through an internalization effect or decrease them because of a diversification effect. The merger also affects loan market competition, which in turn modifies the distribution of bank sizes and aggregate liquidity needs. Mergers among large banks tend to increase aggregate liquidity needs and thus the public provision of liquidity through monetary operations of the central bank.
urn:nbn:de:hebis:30-25993
Keywords: D43; G21; G28; L13; 330; Credit Market Competition; Bank Reserves; Internal Money Market; Banking System Liquidity; Monetary Operations; Bank; Wirtschaftskonzentration; Bankenliquidität; Kreditmarkt; Wettbewerb; Theorie; Industriestaaten